Analisis praktek Samsa>rah (makelar) dalam Jual Beli Sepeda Motor di Kabupaten Bone - Sopyan Sopyan; Yaman Yaman (Institut Agama Islam Negeri (IAIN) Bone, 2019)
The purpose of this study was to find out how brokers practice in buying and selling motorbikes in bone district, how the contract forms in the practice of buying and selling motorbikes in bone district, to find out the views of academics and scholars about the practice of brokers in buying and selling motorbikes in Bone Regency. The results showed that the realtor practice in buying and selling motorbikes in bone district is that the seller gives full authority to the broker to sell motorbikes because the seller does not want to bother with everything, usually the seller only wants to get a clean sale price without deducting costs. In such cases, the seller does not need to meet the buyer because everything will be dealt with by an intermediary trader. An intermediary trader (broker) is not only an intermediary and the seller can also buy and sell motorbikes. Brokers are not just intermediaries in buying and selling activities but can also be buyers because they are interested in the condition of the motorcycle, and will then be sold again so that the intermediary trader will no longer take wages from the sale transaction but will profit from motorcycle sales.